Physicochemical characterization of saccharides powder obtained from yacon roots (Smallanthus sonchifolius) by membrane technology - Maria Julia Ledur Alles (Brazilian Archives of Biology and Technology, 2013)
Fructooligosaccharides (FOS) are food ingredients applied due to combination of prebiotic benefits and interesting technological properties, being used as a sugar substitute. The knowledge of their physicochemical characteristics is important for predicting the stability of the food products where they are added. For this reason, a saccharides powder extracted from yacon (Smallanthus sonchifolius) roots by membrane technology and freeze-dried was investigated. Color, water activity (aw), microstructure by Scanning Electron Microscopy coupled to Energy- dispersive X-ray Spectroscopy (SEM-EDS) and crystallinity by X-ray diffraction were evaluated. The obtained product, containing 19.75% FOS, 36.66% glucose and 43.59% fructose (w/w) was a whitish granulated powder, with aw of 0.284 and CIELAB color coordinates L*, a* and b* of 76.25±1.19, -1.03±0.09 and 1.02±0.03, respectively. It was highly hygroscopic and with agglomeration tendency, confirmed by the formation of bridges between particles on the SEM images. No peaks were identified at X-ray diffractograms, indicating its amorphous characteristics, but sample high hygrospicity and formation of a rigid mass might have hampered a trustable X-ray analysis.